Tell me what you don't know: large language models and the pathologies of intelligence analysis. - Logan, Sarah (Australian Journal of International Affairs, 2024)
This article serves as a warning. Prompted by the likely increase in the reliance on artificial intelligence (AI) in intelligence analysis, it raises grave concerns about the prospect of relying on large language models (LLMs), including in high-stakes contexts such as the state-level resort-to-force decision making that is the focus of this special issue. It begins by identifying the twin informational pathologies that intelligence analysis is subject to by its very nature: information scarcity and epistemic scarcity. It goes on to argue that the use of LLMs would compound these pathologies, attributing this risk to the nature of the international information landscape, especially the rise of private actors in data markets and the changed intelligence environment in the years following September 11. The article concludes by making recommendations for possible responses to the informational risks engendered by the use of LLMs in intelligence analysis, especially in high-stakes contexts.